PENGARUH MANAJEMEN KARIR ORGANISASI, MANAJEMEN KARIR INDIVIDU DAN KOMITMEN KARIR TERHADAP EFEKTIVITAS KARIR KARYAWAN (PADA PT PG RAJAWALI 1 UNIT PG KREBET BARU MALANG) - Reny Afrevita; Abdul Kodir Djaelani; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT:This study aims to determine and analyze the influence of organizational career management, individual career management and career commitment to HR employees. Respondents in this study were employees of PT PG Rajawali1 Unit PG Krebet Baru Malang. The research sample consisted of 61 HR Employees selected by the survey method. This type of research uses quantitative research with data collection methods used are distributing questionnaires and interviews. Data analysis using multiple linier regression analysis with the help of SPSS 14,0  for windows software.The results showed that partially organizational career management variables and individual career management had an effect on the positive direction of employee career effectiveness while the career commitment variable had a negative influence on the career effectiveness of employess of PT PG Rajawali 1 Unit PG Krebet Baru Malang. And simultaneously the organizational career management variables, individual career management and career commitment positively influence the career effectiveness of employess of PT PG Rajawali 1 Unit PG Krebet Baru Malang.Keywords: organizational career management, individual career management and career commitment, career effectiveness.